How Does the Internet Affect Migration Decisions? - Winkler, Hernan (Taylor and Francis, 2017)
This article provides new evidence on the impact of the internet on migration decisions. I find that an increase in internet adoption among migrant-sending countries reduces the stock of migrants from these locations. The results are robust to a number of specifications, including an instrumental variable approach that addresses the endogeneity of internet adoption. The findings suggest that the internet may weaken the importance of push factors in the decision to migrate, and that these effects outweigh declines in mobility costs.